Can the ecological protection red line policy promote food security? -- based on the empirical analysis of land protection in China - Ming Xu; Ming Xu (Frontiers in Environmental Science)
IntroductionChina’s food security is confronted with multiple pressures such as farmland degradation and ecological constraints. As a crucial factor influencing the ecological environment of food, strictly adhering to the ecological protection red line provides an important institutional guarantee for ensuring grain production capacity. In this context, studying the impact of ecological protection red line policy (ERP) on food security (FS) provides a new research direction for developing countries to safeguard national security and protect national food security.MethodsThis paper selects China as the object of quasi-natural experiment research, takes the panel data of 31 provinces from 2005 to 2023 as the research sample, measures the actual development level of China’s food security by using the entropy method, explores the impact of the ecological protection red line policy on food security by using the different-in-differences model, and investigates the heterogeneity between the two by using the quantile model.ResultsThis study demonstrates that the level of food security in China shows a fluctuating upward trend, confirming that the ecological protection red line policy has a significant promoting effect on food security and demonstrates obvious heterogeneous effects. In addition, land transfer (LT) and land reclamation (LR) have strengthened the promoting effect of the ecological protection red line policy, verifying the mediating role between the two.DiscussionThis study not only enriches the research on the relationship between ecological protection red line policy and food security from a theoretical perspective, but also empirically proves that the implementation of ecological protection red line policy is an important policy guideline for enhancing the ecological protection capacity of land and the sustainable capacity of food production. This research not only provides significant reference for improving the construction of China’s food security risk governance system, but also offers valuable experience for achieving national ecological security and food security.